Sixth Five Year Plan Mid-Term Appraisal - Planning Commission, Government of India (Planning Commission, Government of India, 1983)
The Sixth Five Year Plan started in extremely difficult circumstances and had to contend with a number of unfavourable factors. The year 1979-80 witnessed a bad drought which affected agricultural production considerably. Food grain production recorded a heavy fall of 16.8 per cent compared to the previous year. There was an absolute decline in GDP of nearly 5 per cent. As a consequence, savings and investment went down significantly, thereby reducing the resources base of the Sixth Plan. In general, the economy was not in a very satisfactory state and the functioning of the infrastructure, in particular, had been badly affected.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Sixth Five-Year Plan- India; Economic Development